Socket Shield Technique - A New Approach of Immediate Implant Articles Review - Al-Jallad Walid (Journal of Dentistry And Oral Implants, 2019)
Dental implant restoration is challenging procedure when it involve the esthetics zone, and since implant dentistry is prosthodontically driven procedure, care were practice in restoration of missing teeth in esthetics area which will fulfill the objective. Extraction of teeth leave buccal plate bone unsupported and decrease the blood supply and since this plate is very thin resorption will be expected. Different attempt was done in order to prevent this sequence and create natural emergence profile around dental implant prosthesis. Socket preservation procedures were introduced, however in case of ridge deficiencies, hard and soft tissue augmentation procedures are indicated. Socket shield technique meets the demands of minimal invasion, tissue preservation, and no need of bone substitute materials. And can be applied not only for maintaining buccal contour of an edentulous ridge but also for keeping the inter-implant soft and hard tissue In this review paper we present different articles and case report using socket shield technique as treatment protocols and try to explore different protocol are practice in order to achieve high treatment out come with optimal success.
Keywords: Socket-shield technique